Využití prostředků umělé inteligence na kapitálových trzích - Vaško, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zabívá analyzováním možnosti využití umělé inteligence, konkrétně umělých neuronových sítí a fuzzy logiky, na kapitálových trzích jako podpůrný nástroj v rozhodování podniku. K tomu je využito programové prostředí Matlabu. Práce je rozdělena do tří částí. V první se věnuji teoretickým poznatkům, ve druhé stručnému popisu současné situace a ve třetí části aplikuji tyto teoretická východiska do systému.

Diploma thesis deals with analyzing the possibility of using artificial intelligence, specifically artificial neural networks and fuzzy logic, on the capital markets as a tool to support decision making in business. The Matlab software is used for this purpose. The work is divided into three parts. The first part deals with theoretical knowledge, brief description of the current situationin is covered in a second part and the theoretical solutions are applied to the system in the third section.
The Use of Means of Artificial Intelligence for the Decision Making Support on Stock Market
Keywords: Fuzzy logika; umělé neuronové sítě; umělá inteligence; index S&P 500; Matlab; neural network toolbox; NARX; Feed-forward back propagation; money management; klouzavý průměr; směrodatná odchylka; MACD; RSI.; Fuzzy logic; neural network; artificial inteligence; index S&P 500; Matlab; neural network toolbox; NARX; Feed-forward back propagation; money management; moving averige; standard deviation; MACD; RSI.